REACTION AGAINST GLOBAL CONSUMING RITUAL "BLACK FRIDAY" AND CONTRADICTORY PURCHASING BEHAVIOUR - Emine ŞAHİN (Fırat University, 2019)
The success of companies operating in global markets is ensured by the well-known cultural value of the society to sell and its implementation in the local market. In the strategy of postmodern marketing which is replaced massive production and consumption in the modern society more micro perspective is dominant. The companies steer the marketing by considering the cultural differences between consumer groups. It is known that calling Friday which is considered important days by Muslim society as Black Friday causes the reaction in the society. In this research, how perceived the society attitude against Black Friday which is consumption ritual firms used to shape their marketing campaigns in the global market, consumers attitudes against this day and purchasing behaviors, the contradiction between negative attitudes and purchasing behaviors, despite this contradiction, the reasons of purchasing behaviors are aimed to reveal according to Cognitive Contradiction Theory. In this direction, it has been done interview with deeply with ten person who defined by using aim targeted sample identification method in the research where qualitative pattern is used. In this study, half structured interview form has been used and the answers of participants has been analyzed by open coding. In the result of research, it has been identified that participant think most of the society have negative approach on Black Friday because of religious, cultural, ideological, psychological reasons, and most of the participants have negative approach but they demonstrate purchasing behavior in this day and explain this behavior with rational reasons. Obtained findings in this research are useful in the sense of being important to steer marketing campaign applied in the important days by firms are active in the global market.